Insulin Resistant Phenotype of Polycystic Ovary Syndrome does not Seem to be Caused by Variation in FTO - Hatziagelaki, E.; Wagner, R.; Kantartzis, K.; Heni, M.; Linder, K.; Ketterer, C.; Machicao, F.; Stefan, N.; Staiger, H.; Häring, H. U.; Fritsche, A. (Hormone and Metabolic Research, 2012)
Genetic variation in the FTO gene is associated with increased body weight and reduced insulin sensitivity. We investigated whether genetic variation in FTO is associated with polycystic ovary syndrome (PCOS), a condition also characterized by insulin resistance. Furthermore, we tested whether insulin resistance is specifically associated with genetic variation in FTO in women with PCOS. Sixty-two nondiabetic patients with PCOS defined by the Rotterdam criteria were compared to BMI and age-matched women. Each PCOS case was matched to 2 controls. All participants underwent an oral glucose tolerance test and were genotyped for the single nucleotide polymorphism rs8050136 in the FTO gene. There was no difference in the frequency of FTO genotypes between the PCOS and the non-PCOS groups. In non-PCOS participants, genetic variation in FTO is associated with insulin sensitivity (p=0.03). This association remained significant after adjustment for age and/or BMI (p<= 0.03). In subjects with PCOS, however, FTO did not associate with insulin sensitivity (p=0.67). Genetic variation in FTO does not have an impact on insulin sensitivity in women with PCOS and is therefore not involved in the pathogenesis of the insulin resistant phenotype seen in patients with PCOS.
Keywords: FTO; polycystic ovary syndrome (PCOS); insulin resistance; matched case-control study